Emerging roles for the librarian in problem based learning - Kaur, Kiran (University of Malaya, 2004)
Problem-based learning(PBL) has gained recognition in the medical and health sciences in past years. Research has been carried out on the involvement of the library and librarians in PBL implementation. This article reports on the emerging roles for librarians in PBL implementation by rewieing the reasearch in this area during the past 10 years. The initial analysis revealed studies which focussed on the effects of PBL on library usage. However the trend has since evolved to studies on the involvement of librarians in building and implementing the PBL curricula. The aim of this article is to summarize the main findings of research focussed on library involvement in PBL at the faculty and to further provide directions for policy makers and PBL practitioner. Librarians may also find new chalenging roles for themselves within the academia. The studies included in the review were selected by conducting a literature search within identified online databases and selection was done based on empirical studies on PBL in higher learning. The outcomes reveal that librarians may be involved in the planning of PBL, act as facilitators during the implementation, as tutors, as resource professionals and other interesting roles. It is concluded that a framework be proposed for the role of the librarian in the effective implementation of PBL.